1985
DOI: 10.1177/153857448501900204
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Pattern of Atherosclerosis in Africans

Abstract: Despite the very high incidence of arterial hypertension among Africans ath erosclerotic changes linked with prolonged hypertension is not commonly en countered and even then the coronary arteries are known to be spared. Since this seeming protection against atherosclerosis is said to be found among Afri can populations we carried out a study to ascertain the current presentation and pattern of atherosclerosis including fatty streaking of the intima in an indige nous African population. Our findings show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Peripheral artery disease (PAD) is defined as lack of perfusion in the extremities resulting from atherosclerosis. 1 It is characterized by intermittent claudication and an ankle–brachial index of 0.9 or less. A global analysis of the disease in 2000 and 2010 found that about fifth of a billion people in the world have PAD with poorer countries being disproportionately affected.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral artery disease (PAD) is defined as lack of perfusion in the extremities resulting from atherosclerosis. 1 It is characterized by intermittent claudication and an ankle–brachial index of 0.9 or less. A global analysis of the disease in 2000 and 2010 found that about fifth of a billion people in the world have PAD with poorer countries being disproportionately affected.…”
Section: Introductionmentioning
confidence: 99%